Development of prediction model for phosphate in reservoir water system based machine learning algorithms - Latif S.D.; Birima A.H.; Ahmed A.N.; Hatem D.M.; Al-Ansari N.; Fai C.M.; El-Shafie A. (Ain Shams University, 2023)
Decision trees; Eutrophication; Forecasting; Learning systems; Neural networks; Phosphate fertilizers; Predictive analytics; Reservoirs (water); Stochastic systems; Support vector machines; Water pollution; Water quality; Water supply; Conventional modeling; Cross validation; Developed model; Non-point source pollution; Prediction model; Primary sources; Statistical indices; Water quality parameters; Learning algorithms